Avizandum statutes on Scots family law : 2019-2020 - Mair, Jane (Edinburgh University Press, 2019)
Avizandum Statutes on Scots Family Law makes the main statutory provisions relating to adult domestic relation and to child law available in one volume
Includes index of statutes.
Keywords: Domestic relations -- Scotland.